Growing through change: The dynamics of psychological well-being among adolescents following parental divorce - Ainurizan Ridho Rahmatulloh (Academic Journal of Psychology and Counseling, 2026)
Parental divorce represents a significant life transition that can profoundly affect adolescents' psychological well-being. Although a growing body of research has documented the association between parental divorce and adverse psychological outcomes, the subjective processes through which adolescents interpret this experience and reconstruct their well-being remain insufficiently understood. This study aims to explore the dynamics of psychological well-being among adolescents following parental divorce. A qualitative descriptive phenomenological approach was used, involving three adolescents aged 17-18 whose parents had been divorced for at least one year. Data were collected through in-depth interviews and analyzed using phenomenological analysis. The findings indicate that adolescents’ psychological well-being develops through a dynamic process involving changes in post-divorce family relationships, emotional and behavioral adjustment, meaning-making, and future-oriented aspirations. Although Informants also exhibited persistent emotional dysregulation and disrupted future orientation, suggesting a distinct pre-growth state that may precede the consolidation of well-being. These findings highlight that post-divorce psychological well-being is not a uniform outcome but an individualized developmental process. Mental health practitioners are encouraged to complement symptom-reduction approaches with meaning-making facilitation and relational support when working with adolescents from divorced families.